Hubungan Antara Kebersyukuran dan Kepuasan Pernikahan pada Dewasa Awal - Feby Safitri; Intaglia Harsanti; Sendi Satriadi (Publikasi Indonesia, 2022)
This study aims to determine the relationship between gratitude and marriage satisfaction in early adulthood. This study uses quantitative research methods. The sampling technique used in this study was purposive sampling. The sample in this study consisted of 100 early adults. Measurement of marriage satisfaction data was carried out using a marriage satisfaction scale adapted and modified from Rahmi (2015). Measurement of gratitude was carried out using a gratitude scale adapted and modified from Prayogo (2016). The data analysis technique used is the Pearson Product Moment correlation analysis technique. Based on the results of the analysis, it is known that there is a highly significant positive relationship between gratitude and marriage satisfaction in early adulthood with a significance value of 0.000 (p <0.01). These results indicate that the hypothesis that there is a relationship between gratitude and marriage satisfaction in early adulthood can be accepted.